Inhibitory Effects of Cortex Dictamni Aqueous Extract on Dipeptidyl Peptidase I and Chymase Activities and the Screening of Active Ingredients in Cortex Dictamni Based on Molecular Docking Technique - Wang, Qi; Wei, Tao; Zhou, Xiaoying (Journal of Biology and Life Science, 2021)
Dipeptidyl peptidase I (DPPI) and chymase, the granulo-proteases produced and released by mast cells, are important targets of anti-inflammatory drug research and development. Cortex Dictamni is a definite nature drug with anti-inflammatory activity, but the mechanism is unclear and effects of Cortex Dictamni on DPPI and chymase are unknown. This study focuses on effects of Cortex Dictamni aqueous extract (CDAE) on DPPI and chymase activities using cell model, bio-molecular interactions and the Molecular docking study by Discovery Studio (DS) analysis. The results showed that CDAE could significantly inhibit DPPI and chymase activities in vitro and in living rat spleen lymphocytes. Molecular docking simulation demonstrated that Troxerutin, the one of the active compounds of Cortex Dictamni, formed a hydrogen bond with amino acid ILE429 and a strong hydrophobic interaction with TYR64 CYS234 PRO279 ALA382 of DPPI. These interactions allow Troxerutin to form a stable complex with the DPPI, implicating that Troxerutin might be a potential natural inhibitor of DPPI. Dictamnoside M, another active compound of Cortex Dictamni formed hydrogen bonds and hydrophobic interactions within the binding pocket of chymase domain and form a stable complex with the chymase. Dictamnoside M maybe a potential natural inhibitor of chymase. This study suggested a new nature inhibitor Cortex Dictamni and its active components with the anti-inflammatory effects.